Childhood Health Shocks and the Intergenerational Transmission of Inequality - Tine Louise Mundbjerg Eriksen; Amanda Gaulke; Jannet Svensson; Niels Skipper; Peter Rønø Thingholm (Institute of Labor Economics (IZA), 2023)
We examine the role of health shocks in childhood and parental background in transmitting intergenerational inequality. We use Danish administrative registry data (a setting with universal access to health care) and the quasi-random onset of Type 1 Diabetes in childhood to document substantial penalties in adult employment and labor market income at age 30. We document wide disparities in treatment effects and show that high-socioeconomic parents mitigate the adverse impacts of the health shock. This gradient is partly driven by differential impacts on health and human capital across the socioeconomic distribution. Maternal educational attainment matters for adoption of new and more advanced treatment regimens.
Keywords: I12; I14; I24; 330; intergenerational transmission of inequality; childhood health shocks; labor market outcomes